The impact of job similarity along the career path on the firm's promotion strategy - Jakob Infuehr; Sebastian Kronenberger (Schmalenbach Journal of Business Research (SBUR), 2023)
Firms use job promotions to incentivize hard work from low-level employees and to sort employees according to their skills. Since these two functions are often in conflict, a firm's promotion strategy tries to balance them. Our model extends prior research by identifying job similarity between current and future job as a driver of a firm's promotion strategy. When compensation costs are high or external hiring options poor, then higher job similarity leads to fewer internal promotions. Otherwise, higher job similarity can lead to more internal promotions. These results help to explain why firms with different structures or from different industries apply different promotion strategies.
Keywords: 650; Job promotion; Internal hiring; Job similarity; Labor market; Work incentives